Σύγχρονες πόλεις και περιβαλλοντική κοινωνική υπευθυνότητα: σχεδιασμός ενός ολοκληρωμένου πληροφοριακού συστήματος διαχείρισης χρησιμοποιημένων μαγειρικών ελαίων - Αγγελίδου, Μαρία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2015)
The present Master's thesis, “Contemporary Cities and Environmental Social Responsibility: Designing a Complete Informational System of Used Cooking Oil Management” and its counterpart, “A Methodological Framework for the Inquiry and Analysis of Attitudes and Behaviors in the Environment R: The Case of Used Cooking Oil Management” (Droutsas, 2015) comprise a shared research project carried out in the framework of the NTUA Interd isciplinary Program of Postgraduate Studies “Environment and Developm ent”. The dissertation inquires into the issue of the Management of Domestic Used Cooking Oil (UCO) by citizens themselves. Its main objective is to define and analyze the factors which determine the specific environmental behavior of citizens on a demogr aphic, personal and spatial level. The specific object of the research is the recycling of used oil for the purpose of producing biofuel, and pertains to the wider environmental issue of waste material utilization. The specific waste stream of cooking oil was chosen due to the extent of the production and the use of oil in Greek households. Moreover, the human factor was opted as a framework for exploring the UCO management due to the significance of human activities in relation to the environment. A bibli ographical analysis of the reasons for which these choices have necessitated the inquiry into the specific object (the theoretical part) is followed by the research planning and its experimental part. The personal factors - parameters that affect an individu al's behavior were determined on the basis of the theoretical model of the research (TMR), which was constructed according to the theory employed and the interviews conducted at the beginning. The data about social environmental behavior were collected, pr ocessed, analyzed and assessed in reference to the TMR and the main demographic - descriptive characteristics. The tool used for the collection of these data was the questionnaire, while they were processed and analyzed by means of the Statistical Package R and the software of the Geographic Information System ArcGIS. After the data were collected, the answers were processed and turned into arithmetic values. These values were matched to the parameters determined by the TMR, and subsequently the relations amo ng the parameters determining environmental behavior were inquired. The relation of each parameter with “UCO Management” was analyzed in the same vein. What emerged from this process was a set of the most important parameters, which were then inserted into the Regression Analysis. Hence, we can receive results regarding the effect each demographic - descriptive and personal parameter has on an individual's behavior as to their UCO management. These results may well be used either in the design of appropriate practices which would improve social environmental behavior and contribution, or in further research into social environmental behavior.